Studi Komparatif Financial Distress Perusahaan F&B di BEI Berdasarkan Ukuran Perusahaan dengan Metode Altman Z-Score (2020–2024) - Komang Tri Wahyuni (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study aims to analyze and compare the financial distress conditions of food and beverage (F&B) companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period based on firm size. The prediction model employed is the Altman Z-Score, which has been proven for more than 50 years to effectively detect potential bankruptcy with a high degree of accuracy. The research methodology applies a quantitative approach with a sample of 20 F&B companies selected through purposive sampling. Secondary data were obtained from annual financial reports available on the IDX. The analysis was conducted by calculating the Altman Z-Score values for each company, followed by a comparative test (independent sample t-test) to examine the differences in financial distress conditions between large and small firms. The findings reveal that small F&B companies have an average Z-Score of 4.41 (safe zone), while large companies record a score of 2.88 (grey zone). These results indicate that during the study period, small firms were relatively more adaptive and efficient in managing costs, whereas large firms were more exposed to pressures from fixed expenses and high leverage. Thus, financial distress in the F&B sector is significantly influenced by firm size. The study provides several recommendations: (1) large firms should improve cost efficiency and reduce reliance on debt; (2) small firms need to strengthen capitalization and corporate governance to ensure long-term sustainability; (3) investors should not only rely on firm size but also consider Altman Z-Score predictions when making investment decisions. Future research is recommended to apply other prediction models such as Springate or Grover and extend the sample to sectors beyond F&B to provide a more comprehensive understanding.